PERFORMANCE ANALYSIS OF SECURED COMMUNICATION WITH CRYPTOGRAPHY USING FIBONACCI SERIES - MS. NAMITA GEORGE GONSALVES; MS. NOOTANA G BHAT (International Journal of Innovations in Engineering Research and Technology, 2021)
Data security has been a major concern in the today’s information technology era. Especially it becomes serious in the cloud environment because the data is located in different places all over the world. Encryption has come up as a solution and different encryption algorithms play an important role in data security on cloud. Encryption algorithms areused to ensure the security of data in cloud. The purpose of securing data is that only concerned and authorized users can access it. In this paper we describes the basic characteristics (Key Length, File size) of symmetric Fibonacci Cryptography, Asymmetric RSA algorithms.